2020
DOI: 10.1093/eurheartj/ehaa408
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and clinical significance of myocardial injury in patients with severe coronavirus disease 2019

Abstract: Aims To investigate the characteristics and clinical significance of myocardial injury in patients with severe coronavirus disease 2019 (COVID-19). Methods and results We enrolled 671 eligible hospitalized patients with severe COVID-19 from 1 January to 23 February 2020, with a median age of 63 years. Clinical, laboratory, and treatment data were collected and compared between patients who died and survivors. Risk factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
462
7
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(516 citation statements)
references
References 20 publications
29
462
7
18
Order By: Relevance
“…In our study, there was no difference in the outcome between non-comorbidity group and diabetes only group. Shi et al reported that even thought COVID-19 patients with diabetes had worse outcomes; diabetes was not independently associated with in-hospital death, which was consistent with our results [16]. Besides, most laboratory results were comparable between non-comorbidity group and diabetes only group except CRP, albumin, sodium, urea nitrogen, HDL-C and, of course blood glucose.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, there was no difference in the outcome between non-comorbidity group and diabetes only group. Shi et al reported that even thought COVID-19 patients with diabetes had worse outcomes; diabetes was not independently associated with in-hospital death, which was consistent with our results [16]. Besides, most laboratory results were comparable between non-comorbidity group and diabetes only group except CRP, albumin, sodium, urea nitrogen, HDL-C and, of course blood glucose.…”
Section: Discussionsupporting
confidence: 91%
“…Patients of diabetes with comorbidity was 10 years older than the patients who had no comorbidity expect diabetes, furthermore, age ≥65 was associated with greater risk of development of death [4]. As described above, patients with hypertension, CVD were more likely to develop severe cases [4,16,17,20]. Furthermore, our analysis indicated that age, hypertension, CKD, CVD were the risk factors for mortality of COVID-19.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studied had clearly demonstrated that patients with cardiopulmonary comorbidities had adverse outcomes, including progression into cardiac injury and death [26][27][28]. The potential mechanisms were also proposed based on the observations of several molecular and pathology studies [29][30][31]. Despite the fact that HCQ/CQ were commonly used for rheumatoid arthritis and systemic lupus erythematosus in the general population, there has been major concern with widespread use of these medications for COVID-19 due to possible QTc prolongation and induction of life-threatening arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Bhatraju et al recently reported that 71% of 24 critically ill COVID-19 patients required vasopressor infusion more than 12 hours after intubation [1]. Many studies have reported that myocardial injury and heart failure are frequent in COVID-19 patients and are common causes of death [2,3]. Spectrum of the COVID-19 cardiovascular syndrome is large with different potential mechanisms supporting acute myocardial injury [4].…”
Section: Introductionmentioning
confidence: 99%